A proposed FPGA Architecture Design - Mulualem, Yelkal; Sirajudeen, M.Mohamed (IJRDO-Journal of Applied Science, 2015)
This research paper discuss with a general over view of FPGAs particularly, Architectural Description of Virtex-4 FPGA and Verilog Hardware Description Language of the proposed work. It has also depth description of design of the new developed FPGA Architectural. FPGA architecture design and development approach used in this paper is followed top-down approach. Later the design and implementation of the four modules, namely, Top-Module, Read-Code Word Module, ReadAveraged Sample Module and Decoder-Module will be discussed with the necessary information’s.